Sorption and desorption of lead on 5-amino-1,3,4-thiadiazole-2-thiol immobilized silica gel by flame atomic absorption spectrometry (FAAS) - Dogan, Canan Ekinci; Akcin, Goksel (TAYLOR & FRANCIS INC, 2008)
Silica gel was modified by 5-amino-1,3,4-thiadiazole-2-thiol via homogeneous routes to obtain immobilized silica gel sorbent (ATT-immobilized silica gel). This sorbent was characterized using a variety of physical chemical techniques including, high resolution solid state C-13 CP/MAS NMR, X-ray photoelectron spectroscopy (XPS), thermal analysis (TGA and DTA), elemental analysis, and BET surface analysis, as well as infrared spectroscopy (FTIR). The support was used for sorption and desorption of leadions by silica gel modified with 5-amino-1,3,4-thiadiazole-2-thiol from aquatic samples and their determination with FAAS. Lead ions can be desorbed with 0.001mol dm(-3) EDTA. The sorption capacity for lead ions is found to be in the range of 48.20-49.50 mu mol g(-1)(about 10.14mg L-1) of chelating matrix. Tolerance limits for electrolytes in the sorption of lead are reported. Experimental data obtained from batch equilibrium tests have also been analyzed by Langmuir isotherm and the Freundlich equation. Theoretically, maximum monolayer adsorption capacity was obtained to be 14.28 for ATT-immobilized silica gel. Pb(II) sorption on ATT-immobilized silica gel was found favorable according to the Langmuir isotherm and the Freundlich equation.
Keywords: adsorption isotherms; FAAS; lead; immobilized silica gel; solid phase extraction; 5-amino-1,3,4-thiadiazole-2-thiol; SOLID-PHASE EXTRACTION; HEAVY-METAL IONS; PRECONCENTRATION; SURFACE; COMPLEXES; MANGANESE; VANADIUM; Chemistry; Instruments & Instrumentation